2022
DOI: 10.3390/nu14102144
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of “Diet–Smoking–Gender” Three-Way Interactions on Cognitive Impairment among Chinese Older Adults

Abstract: Investigations on gender variations in the risk factors of cognitive impairment are required to promote future precision medicine among older adults, as well as to contribute to a better understanding of the “male–female health-survival paradox”. With this study, we aimed to investigate the effects of “diet–smoking–gender” three-way interactions on cognitive impairments among Chinese older adults. We conducted a 16-year prospective cohort study among 15,953, 15,555, 16,849, 9716, 7116, and 13,165 older adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…According to previous studies ( 11 , 28 30 ), this study applied DDS to evaluate older adults’ dietary diversity. Specific intake frequencies and scoring criteria are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies ( 11 , 28 30 ), this study applied DDS to evaluate older adults’ dietary diversity. Specific intake frequencies and scoring criteria are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…However, regarding smoking and drinking status, the results of this study showed that individuals who smoked less and drank less frequently were more susceptible to EPs, contradicting previous studies. We attribute this discrepancy to the higher proportion of female individuals in this study, as generally, fewer Chinese females have habits of smoking and drinking in daily life (49,50). Additionally, studies have reported that acetylcholine contributes to regulating brain homeostasis and shaping synaptic neuron transmission and neurotransmitter levels (51).…”
Section: Discussionmentioning
confidence: 83%
“…Many factors can attribute to such difference, for instance, males are more likely to possess unhealthy behaviors than females, including but not limited to lack of vegetables and fruits in diet and fewer physical activity. Such factors could contribute to higher prevalence of many metabolic diseases in males than females, including dyslipidemia (104)(105)(106)(107)(108). Researches showed that estrogen changes the vascular permeability by increasing nitrous oxide production which retains a healthful lipoprotein profile (109,110).…”
Section: Discussionmentioning
confidence: 99%